1995
DOI: 10.1128/jvi.69.10.6567-6571.1995
|View full text |Cite
|
Sign up to set email alerts
|

Modest truncation of the major capsid protein abrogates B19 parvovirus capsid formation

Abstract: In vitro studies have suggested an important role for the minor capsid protein (VP1) unique region and the junction between VP1 and the major capsid protein (VP2) in the neutralizing immune response to B19 parvovirus. We investigated the role of the NH 2 -terminal region of the major structural protein in capsid structure by expressing progressively more truncated versions of the VP2 gene followed by analysis using immunoblotting and electron microscopy of density gradient-purified particles. Deletion of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Here we confirm the relevance of this region in capsid assembly and morphogenesis. In contrast to our results, recent findings for B19 (10) have shown that most of the amino terminus (up to 25 aa), including the polyglycine region, can be removed without affecting capsid self-assembly. These differences are more significant if we consider that in B19 the amino terminus adjacent to the glycine-rich region is much shorter and the polyglycine region, located between aa 12 and 17, is within the initial 25 residues that can be deleted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here we confirm the relevance of this region in capsid assembly and morphogenesis. In contrast to our results, recent findings for B19 (10) have shown that most of the amino terminus (up to 25 aa), including the polyglycine region, can be removed without affecting capsid self-assembly. These differences are more significant if we consider that in B19 the amino terminus adjacent to the glycine-rich region is much shorter and the polyglycine region, located between aa 12 and 17, is within the initial 25 residues that can be deleted.…”
Section: Discussioncontrasting
confidence: 99%
“…The disorder of the amino termini of CPV VP2 was assumed to be due to association of this region with the viral DNA (10). For this reason, no participation of the amino-terminal domain in capsid conformation and morphogenesis was expected.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that other mutations within the A. sylvaticus or R. norvegicus EVE sequences or our other repair sequences prevented assembly. Studies with extant parvoviruses show that single point mutations within the major capsid protein can block capsid assembly, especially when they occur within the well-conserved residues that form the interior of the capsid or are near the 5-fold axis (36)(37)(38)(39). Expressing many of the less conserved exterior surface loops in place of the equivalent sequences of the CPV capsid allowed the chimeras to assemble (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to AAV, it has been shown that the capsids of these parvoviruses can be formed in the presence of the major capsid protein, VP2, alone (4,9). In previous work, it was shown that the most N-terminal 25amino-acid residues of VP2 of B19 were not required for capsid assembly (10). Amino acid sequence alignment of VP2 protein of B19 with AAV indicates that the minimal protein capable of B19 capsid formation corresponds to VP3 rather than VP2 of AAV (data not shown).…”
mentioning
confidence: 99%